Time to Treatment Initiation and Survival in Adult Localized High-Grade Bone Sarcoma. (5th May 2020) - Lawrenz, Joshua M.; Featherall, Joseph; Curtis, Gannon L.; George, Jaiben; Jin, Yuxuan; Anderson, Peter M.; Shepard, Dale R.; Reith, John D.; Rubin, Brian P.; Nystrom, Lukas M.; Mesko, Nathan W.
Abstract : Objective . Few studies have evaluated the prognostic implication of the length of time from diagnosis to treatment initiation in bone sarcoma. The purpose of this study is to determine if time to treatment initiation (TTI) influences overall survival in adults diagnosed with primary bone sarcoma. Methods . A retrospective analysis of the National Cancer Database identified 2, 122 patients who met inclusion criteria with localized, high-grade bone sarcoma diagnosed between 2004 and 2012. TTI was defined as length of time in days from diagnosis to initiation of treatment. Patient, disease-specific, and healthcare-related factors were also assessed for their association with overall survival. Kruskal-Wallis analysis was utilized for univariate analysis, and Cox regression modeling identified covariates associated with overall survival. Results . Any 10-day increase in TTI was not associated with decreased overall survival (hazard ratio (HR) = 1.00; P = 0.72 ). No differences in survival were detected at 1 year, 5 years, and 10 years, when comparing patients with TTI = 14, 30, 60, 90, and 150 days. Decreased survival was significantly associated P < 0.05 with patient ages of 51–70 years (HR = 1.66; P = 0.004 ) and > 71 years (HR = 2.89; P < 0.001 ), Charlson/Deyo score ≥2 (HR = 2.02; P < 0.001 ), pelvic tumor site (HR = 1.58; P < 0.001 ), tumor size >8 cm (HR = 1.52; P < 0.001 ), radiation (HR = 1.81; P < 0.001 ) as index treatment, and residing a distance of 51–100 miles from the treatment center (HR = 1.30; P = 0.012 ). Increased survival was significantly associated P < 0.05 with chordoma (HR = 0.27; P = 0.010 ), chondrosarcoma (HR = 0.75; P = 0.002 ), treatment at an academic center (HR = 0.64; P = 0.039 ), and a private (HR = 0.67; P = 0.006 ) or Medicare (HR = 0.71; P = 0.043 ) insurer. A transition in care was not associated with a survival disadvantage (HR = 0.90; P = 0.14 ). Conclusions . Longer TTI was not associated with decreased overall survival in localized, high-grade primary bone sarcoma in adults. This is important in counseling patients, who may delay treatment to receive a second opinion or seek referral to a higher volume sarcoma center.